“Diseño de un producto turístico en el emprendimiento Apiloja (Cotopaxi)”. - Piedra Cisneros, Jhonny Alexander (2024)
This project corresponds to the “Design of a tourism product in the Apiloja enterprise” which is located in the Latacunga canton, Santan sector, in order to promote experiential tourism, through the visit and tour of tourists to the facilities of the place, the The project has a qualitative approach since through it the characteristics of the tourist are known, such as their motivations and preferences when visiting a certain place. The design of the tourism product was developed based on 3 strategically established objectives, the first, the current tourist situation was determined through a diagnosis, through a bibliographic analysis, in order to understand the tourist situation, this was carried out through a review bibliographic, in addition to the support in primary and secondary sources, where information was collected in order to know what the political division of the Latacunga canton is, and in this way to know if there is any tourist place adjacent to the enterprise, in the same way a mapping was done of actors, in this case 2, the owner of Apiloja and the owner of another establishment with similar characteristics, with whom an interview was conducted, to have a background of the tourist situation. The second objective was to design the tourism product applying the Promperú methodology, which proposes a 4-phase manual, which are: Analysis of the tourist destination, where a formula intended for infinite populations was used to calculate the size of the sample that In this case it was 385 people and a survey was carried out with 21 questions to obtain a profile of the tourist, Conceptualization of the tourism product, at this point question No. 15 of the survey was used, the activities that attract the most were defined. to the visitor, in this case 4 and I evaluate them using the matrices in the manual, Design of the tourism product, in this section 7 attractions that make up the tourism product were defined, in order to develop a sketch of the establishment and Action Plan for the tourism product. In this item, the actions, time and those responsible for executing the project are detailed. Once implemented, the last objective was to create promotion and dissemination strategies, using the SWOT, MEFI, MEFE and CROSS SWOT matrices. Through the use of these matrices, it was possible to obtain a clear overview of the situation, both external and internal. , in the field of production and supply, resulting in 8 strategies that solve the marketing needs of the enterprise's products. With the execution of this project, it is concluded that the creation of a tourism product in the Apiloja venture will be an impetus for the development of experiential tourism, since significant experiences will be obtained in the field of beekeeping, as well as marketing strategies. of products will be a significant support as they will help offer and sell Apiloja products.